Quality of snow deposited in urban areas : Storage, load assessment and release of selected pollutants with snowmelt - Vijayan, Arya (Luleå tekniska universitet, Arkitektur och vatten, 2020)
Snow deposited in urban areas is exposed to pollutants originating from traffic, wet and dry atmospheric deposition, de-icing chemicals and traction materials. The conventional pollutants found in urban snow include solids (TSS), metals (Zn, Cu, Cd, Pb, etc.), Polycyclic Aromatic Hydrocarbons (PAHs), and chlorides. Microplastics (MPs) are emerging pollutants of interest and their presence in urban snow was reported only recently. The pollutants accumulate in snow deposits over time and may be released when snow melts, and the resulting snowmelt may carry pollutants to the receiving waters. Understanding the concentrations and mass loads of pollutants in snow and pollutant behaviour during snowmelt is helpful for planning and developing site-specific snow management practices. The overall aim of this thesis was to evaluate the quality of snow in urban areas, with respect to: (i) quantity of metals, PAHs and MPs in urban snow storage piles and roadside snowbanks, (ii) compare the quality of snow collected in the same catchment during repeated sampling campaigns and evaluate the effect of the sampling design on estimation of pollutant loads in snow piles, and (iii) investigate the pollutant release patterns and temporal variations in their concentrations in water leaving the melting snow piles (in laboratory). For such studies, snow samples were collected from snow storage piles in Frihamnen (a port facility in Stockholm, Sweden) and roadside snowbanks in Luleå and Umeå cities in Northern Sweden. The quality of snow collected in the three study areas varied considerably, because of differences in such area characteristics as the annual precipitation and snowfall, the population, average daily traffic, land use activities, and snow management activities. The average values of major parameters in analysed snow samples were as follows: TSS - 1500 mg/L, conductivity- 2.1 mS/cm, Zn – 870 µg/L, Cu – 240 µg/L, Cd – 0.48 µg/L, Cr – 120 µg/L, Pb – 50 µg/L and the sum of 16 PAHs – 3.5 µg/L. Microplastics were abundant in ...